"The dilemmas of the Israeli reality and the option of war" - Basheer Hadi Abdul Razzaq Ali Al-Zubaidi (Tikrit Journal For Political Science, 2015)
The Arab-Israeli conflict is among the longest and most complex conflicts in the world at the present time. It is a struggle that goes beyond being a struggle over borders or a dispute over influence. It is a struggle for existence in every sense of the word. Since its inception (Israel) in 1948, it has become one of the regional powers whose political movement towards the Arab world is determined by the sum of the internal and external factors and variables affecting it. Others, which reflects negatively on the regional strategic situation. Despite the so-called peace settlement between (Israel) and some Arab countries, and the geopolitical changes that have afflicted the region and rocked it recently, which indicates a decline in the threat of Arab countries to the Israeli presence at the present time and in the foreseeable future, the amount of spending allocated by (Israel) The favor of its military has continued to mount.